282 Follow-up of hospitalized COVID-19 survivors: assessment of short- and long-term cardiovascular sequelae after SARS-CoV-2 infection. (8th December 2021) - Birtolo, Lucia Ilaria; Prosperi, Silvia; Monosilio, Sara; Cimino, Sara; Filomena, Domenico; Alfarano, Maria; Manzi, Giovanna; Neccia, Matteo; Papa, Silvia; Passarelli, Ilaria; De Persis, Francesca; Luca, Alessandra De; et al.
Abstract: Aims: Cardiovascular sequelae in COVID-19 survivors remain largely unclear and can potentially go unrecognized. Reports on follow-up focused on cardiovascular evaluation after hospital discharge are currently scarce. Aim of this prospective study was to assess cardiovascular sequelae in previously hospitalized COVID-19 survivors. Methods and results: The study was conducted at 'Sapienza' University of Rome—Policlinico 'Umberto I'. After 2 months from discharge, n = 230 COVID-19 survivors underwent a follow-up visit at a dedicated 'post-COVID Outpatient Clinic'. A cardiovascular evaluation including electrocardiogram (ECG), Troponin and echocardiography was performed. Further tests were requested when clinically indicated. Medical history, symptoms, arterial-blood gas, blood tests, chest computed tomography, and treatment of both in-hospital and follow-up evaluation were recorded. A 1-year telephone follow-up was performed. A total of 36 (16%) COVID-19 survivors showed persistence or delayed onset of cardiovascular disease at 2-months follow-up visit. Persistent condition was recorded in 62% of survivors who experienced an in-hospital cardiovascular disease. Delayed cardiovascular involvement included: myocarditis, pericarditis, ventricular disfunction, new onset of systemic hypertension and arrhythmias. At 1-year telephone follow-up, 105 (45%) survivors reported persistent symptoms, with dyspnoea and fatigue being the most frequent. 60% of survivors showed persistent chest CT abnormalities and among those 28% complained of persistent cardiopulmonary symptoms at long term follow-up. Conclusions: Our preliminary data showed persistent or delayed onset of cardiovascular involvement (16%) at short-term follow-up and persistent symptoms (45%) at long-term follow-up. These findings suggest the need for monitoring COVID-19 survivors.